Effect of nitrogen doses on morphological parameters and content of cumarina in accesses of Mikania glomerata Sprengel (guaco) - Alves, Luciano; Deschamps, Cícero (Revista de Ciências Agroveterinárias, 2025)
Nitrogen plays a role in the synthesis of secondary metabolites. Guaco (Mikania glomerata Sprengel is a medicinal species used in the treatment of respiratory diseases due to its content of coumarin (1,2-benzopyrone). The aim of this study was to evaluate the effect of ammonium nitrate doses on morphological parameters and coumarin content in two guaco accessions. The experiment was conducted in a randomized block design, with a 2 x 5 factorial arrangement, where the treatments were the combination of two guaco accessions and five fertilization doses, including a control. The fertilization levels were 0 g pl1; 35 g pl-1; 70 g pl-1; 140 g pl-1; and 280 g pl-1. At planting, 35 g pl-1 was applied as a top-dressing, with the remaining doses split into three applications at 30, 60, and 90 days after planting. The experiment was conducted for 18 months, with two analyses performed: one at 6 months after planting and another with plants that remained in the field for 18 months. After these periods, the following parameters were evaluated: dry mass of leaves, branches, and total; leaf area; and coumarin content. For all parameters analyzed and at both harvest times, a quadratic effect was observed in response to nitrogen doses for all variables studied. Nitrogen doses influenced the coumarin content in the evaluated accessions. The doses of maximum technical efficiency varied among the evaluated parameters, harvest times, and accessions. In the six-month cultivation, the guaco accessions showed higher coumarin values in kg ha-1, as well as within the standards required by ANVISA, when cultivated with doses of 130 g N pl-1 for accession G1 and 106 g N pl -1 for accession G2.